The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1152/ajpendo.00383.2021
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol and RSPO3 regulate vertebral trabecular bone mass independent of each other

Abstract: Osteoporosis is an age-dependent serious skeletal disease that leads to great suffering for the patient and high social costs, especially as the global population reaches higher age. Decreasing estrogen levels after menopause result in a substantial bone loss and increased fracture risk, while estrogen treatment improves bone mass in women. RSPO3, a secreted protein that modulates WNT signaling, increases trabecular bone mass and strength in the vertebrae of mice, and is associated with trabecular density and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
(58 reference statements)
2
2
0
Order By: Relevance
“…Very surprisingly, however, and although the basal expression level of Rspo3 and the efficiency of deletion in long bones and vertebrae were similar ( Figure 3a and Figure 4a ), L5 μCT analysis showed a significant decrease in BV/TV, Tb.N, Tb.Th, and Conn.D accompanied by a marked increase in Tb.Sp. and SMI in Rspo3-OB-cKO compared with their control ( Rspo3 fl ) male and female littermates ( Figure 4b ), confirming a recent report ( Nilsson et al, 2022 ). Bone histomorphometry analysis showed that structural parameters were also significantly decreased but only in Rspo3-OB-cKO males compared with the control group ( Figure 4c–d and Supplementary file 6 ).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Very surprisingly, however, and although the basal expression level of Rspo3 and the efficiency of deletion in long bones and vertebrae were similar ( Figure 3a and Figure 4a ), L5 μCT analysis showed a significant decrease in BV/TV, Tb.N, Tb.Th, and Conn.D accompanied by a marked increase in Tb.Sp. and SMI in Rspo3-OB-cKO compared with their control ( Rspo3 fl ) male and female littermates ( Figure 4b ), confirming a recent report ( Nilsson et al, 2022 ). Bone histomorphometry analysis showed that structural parameters were also significantly decreased but only in Rspo3-OB-cKO males compared with the control group ( Figure 4c–d and Supplementary file 6 ).…”
Section: Resultssupporting
confidence: 90%
“…In the current studies, we have further investigated the role of Rspo3 in skeletal homeostasis. We found that if, as recently reported ( Nilsson et al, 2021 ; Nilsson et al, 2022 ), targeted deletion of Rspo3 in Runx2 + cells decreases bone mass in the axial skeleton, both global Rspo3 haplo-insufficiency and targeted deletion of Rspo3 in Runx2 + osteoblast precursors lead to a marked increase in trabecular bone mass in the appendicular skeleton in both male and female mice, mainly as a result of increased bone formation. Mechanistically, we found that Rspo3 deletion leads to increased Erk phosphorylation, and, similar to increased Rspo3, stabilization of β-catenin and, activation of Wnt signaling, revealing a novel Rspo3/Erk/Wnt signaling axis that contributes to the regulation of skeletal homeostasis.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations